Efficiency Evaluation of Health services in Ali Al- Gharbi District in 2019 and future needs - Taher Jassim , Shaima; Ismail Othman, Assist.Prof. Dr. Osama (Basra studies journal, 2022)
This The topic of the research focused on the study of health services in the city of Ali Al-Gharbi in 2019. The study revealed the population growth in the city and population size in study year, which was 18710 persons. The research dealt with issue of the efficiency of health services based on some of human, numerical and cadastral indicators and public and compare it with local planning standards to identify the amount of deficit and surplus of health services reaching to the current need of health services, then the future need after predicting the future area and future population size for the target year set in 2030 deduce to study it presence loss. In a number institutions health compared to the number of served population, there is a shortage of medical devices, medicines and doctors, as the sample members indicated their dissatisfaction with the health services provided to them.